PERANCANGAN ALAT BANTU KERJA PADA PROSES PAINTING BOF NONFLIP DI PT XYZ - Siswanto, Alvin Ari; Arista, Anggia (LPPM Universitas Putera Batam, 2023)
All products must have aesthetic value in order to attract customer interest, one of which is to apply color coating by carrying out the painting process. This research was conducted at the painting department at PT XYZ where the color coating process on nonflip bof products was carried out without the use of tools according to product specifications, as a result the product fell due to wind pressure from the spray gun causing the nonflip bof product to become deformed and the target was not reached. Based on this, the researcher intends to conduct research on the design of work aids for the painting process of nonflip bof products using the Design for Manufacturing and Assembly (DFMA) method. Based on the DFMA analysis, the design of this tool was assembled with a total of 10 components and a manufacturing cost of IDR 2,608,163 and a manufacturing time of 3.82 hours. From the test results after using the tools from the design results, it was found that the painting process of nonflip bof only took 3.64 minutes for one time painting process of 20 units of nonflip bof products with a total output of 1 working day producing 1,860 units.